Citation Analysis of Ph.D. Theses at Faculty of Science, University of Ibadan, Nigeria - Malik Oyewale Salami; Wole Michael Olatokun (Issues in Science and Technology Librarianship, 2018)
The authors analyzed 21,005 citations from 124 Ph.D. theses submitted to ten departments in the Faculty of Science, University of Ibadan, in Nigeria, during the period 2006 to 2013. The overall analysis of the cited information sources revealed that journals (67.6%) were the most cited sources, followed by books/monographs (13.6%), and conference papers (2.6%). The cited journals were predominantly non-Nigerian journals. This study also analyzed and compared the characteristics and variations of the cited literature across the ten departments. In addition, evaluation of the availability of cited journals in the University Library showed that the library is deficient in providing adequate journals for students' scholarship and research.